Green Tea Epigallocatechin-3-Gallate Regulates Autophagy in Male and Female Reproductive Cancer - Sze Wan Hung; Yiran Li; Xiaoyan Chen; Xiaoyan Chen; Kai On Chu; Yiwei Zhao; Yiwei Zhao; Yingyu Liu; Yingyu Liu; Xi Guo; Gene Chi-Wai Man; Gene Chi-Wai Man; et al. (Frontiers Media S.A., 2022)
With a rich abundance of natural polyphenols, green tea has become one of the most popular and healthiest nonalcoholic beverages being consumed worldwide. Epigallocatechin-3-gallate (EGCG) is the predominant catechin found in green tea, which has been shown to promote numerous health benefits, including metabolic regulation, antioxidant, anti-inflammatory, and anticancer. Clinical studies have also shown the inhibitory effects of EGCG on cancers of the male and female reproductive system, including ovarian, cervical, endometrial, breast, testicular, and prostate cancers. Autophagy is a natural, self-degradation process that serves important functions in both tumor suppression and tumor cell survival. Naturally derived products have the potential to be an effective and safe alternative in balancing autophagy and maintaining homeostasis during tumor development. Although EGCG has been shown to play a critical role in the suppression of multiple cancers, its role as autophagy modulator in cancers of the male and female reproductive system remains to be fully discussed. Herein, we aim to provide an overview of the current knowledge of EGCG in targeting autophagy and its related signaling mechanism in reproductive cancers. Effects of EGCG on regulating autophagy toward reproductive cancers as a single therapy or cotreatment with other chemotherapies will be reviewed and compared. Additionally, the underlying mechanisms and crosstalk of EGCG between autophagy and other cellular processes, such as reactive oxidative stress, ER stress, angiogenesis, and apoptosis, will be summarized. The present review will help to shed light on the significance of green tea as a potential therapeutic treatment for reproductive cancers through regulating autophagy.